Effect of post annealing thermal heating on Cu2ZnSnS4 solar cells processed by sputtering technique. (1st May 2022) - Sanchez, M.F.; Sanchez, T.G.; Courel, Maykel; Reyes-Vallejo, O.; Sanchez, Y.; Saucedo, E.; Sebastian, P.J.
Highlights: Thermal annealing of Cu2 ZnSnS4 solar cell in air improved the solar cell characteristics. The band gap of Cu2 ZnSnS4 decreased with thermal annealing in air. Cd diffusion was observed from CdS to to Cu2 ZnSnS4 . Increase in external quantum efficiency was observed with hot-plate annealing. Abstract: In this work, a detailed study of the effect of thermal treatment (hot plate) on a Mo/CZTS/CdS/i-ZnO/ITO solar cell was carried out, which promotes the diffusion of the Cd contained in the window layer of CdS towards the absorber layer of CZTS. The thermal treatment of the Mo/CZTS/CdS/i-ZnO/ITO solar cell was carried out at temperatures ranging from 100 °C to 400 °C and times varying from 3 to 15 min in air atmosphere. The CZTS was grown from deposits of metallic precursors (Cu/Sn/Cu/Zn) by sputtering and annealing at two ramps: 200° C for 45 min with an argon flow of 1 mbar and 550 °C for 5 min at 1 bar in an atmosphere of S + Sn. For the complete solar cells with a hotplate treatment of 280 °C for 6 min an increase of 2.7% to 5.2% of conversion efficiency was observed compared to the solar cell without hotplate treatment. The band gap CZTS decreased from 1.56 to 1.43 eV and Jsc increased from 12.0 mA/cm 2 to 15.4 mA/cm 2 .